Protein tyrosine phosphatase activity in the neural crest is essential for normal heart and skull development - Tomoki Nakamura; James Gulick; Melissa C. Colbert; Jeffrey Robbins (2009)
Mutations within the protein tyrosine phosphatase, SHP2, which is encoded by PTPN11 , cause a significant proportion of Noonan syndrome (NS) cases, typically presenting with both cardiac disease and craniofacial abnormalities. Neural crest cells (NCCs) participate in both heart and skull formation, but the role of SHP2 signaling in NCC has not yet been determined. To gain insight into the role of SHP2 in NCC function, we ablated PTPN11 specifically in premigratory NCCs. SHP2-deficient NCCs initially exhibited normal migratory and proliferative patterns, but in the developing heart failed to migrate into the developing outflow tract. The embryos displayed persistent truncus arteriosus and abnormalities of the great vessels. The craniofacial deficits were even more pronounced, with large portions of the face and cranium affected, including the mandible and frontal and nasal bones. The data show that SHP2 activity in the NCC is essential for normal migration and differentiation into the diverse lineages found in the heart and skull and demonstrate the importance of NCC-based normal SHP2 activity in both heart and skull development, providing insight into the syndromic presentation characteristic of NS.